Risk factors for acute liver failure among inpatients with anti-tuberculosis drug-induced liver injury. Issue 1 (January 2020) - Wang, Shuting; Shangguan, Yanwan; Ding, Cheng; Li, Pengcheng; Ji, Zhongkang; Shao, Jundan; Fang, Hong; Yang, Meifang; Shi, Pei; Wu, Jie; Ren, Jingjing; Yang, Shigui; et al.
Objective: To analyze the clinical and laboratory features and determine the predictors of acute liver failure (ALF) among inpatients with anti-tuberculosis (TB) drug-induced liver injury (DILI). Method: Patients diagnosed with anti-TB DILI from 2010 to 2016 at The First Affiliated Hospital of Zhejiang University were retrospectively included in this study. Demographic and clinical data were collected by reviewing electronic medical records. Results: Among 155 inpatients with anti-TB DILI, 55 (35.48%) developed ALF, with an overall mortality of 9.68%. The median time to DILI onset was significantly longer in the ALF compared with the non-ALF group (51 versus 24 days). Eighty-three patients (53.55%) developed DILI (53.55%) within the first month of anti-TB treatment, and 60% of ALF cases occurred within 2 months. Multivariable models for ALF incorporating aspartate aminotransferase, total bilirubin, platelets, white blood cell count, and pre-existing hepatitis yielded a concordance (C-statistic) of 98.93%. Conclusions: The results of this study suggest that approximately half of all cases of DILI occur within the first month, while 60% of ALF cases occur within 2 months. Elevated total bilirubin, aspartate aminotransferase, white blood cell count, pre-existing hepatitis, and low platelet count are independent risk factors for the development of anti-TB drug-induced ALF.